2018
DOI: 10.1002/job.2324
|View full text |Cite
|
Sign up to set email alerts
|

Time‐based differences in the effects of positive and negative affectivity on perceived supervisor support and organizational commitment among newcomers

Abstract: Summary Building on the broaden‐and‐build theory and research on the negativity bias, this study examines how trait affectivity, as a stable predisposition predicting the pattern of emotional responding, shapes newcomers' perceptions of supervisor support and experience of organizational commitment. Using latent growth modeling and data collected at four points in time from newcomers (N = 158), we found the initial level of perceived supervisor support to mediate a negative relationship between negative affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 140 publications
0
14
0
Order By: Relevance
“…Individuals with high levels of perceived insider status, because they have a sense of belonging within their organisation, behave according to organisational interests even without being forced by formal contracts (Ding & Chang, ). However, individuals with high levels of normative commitment are more likely to be formally guided by job descriptions or supervisory directions (Vandenberghe et al, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with high levels of perceived insider status, because they have a sense of belonging within their organisation, behave according to organisational interests even without being forced by formal contracts (Ding & Chang, ). However, individuals with high levels of normative commitment are more likely to be formally guided by job descriptions or supervisory directions (Vandenberghe et al, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…However, individuals with high levels of normative commitment are more likely to be formally guided by job descriptions or supervisory directions (Vandenberghe et al, 2019).…”
Section: Perceived Insider Status As a Mediatormentioning
confidence: 99%
“…Considering that extraverts are more likely to develop and participate in interpersonal activities (Cullen-Lester et al, 2016;Methot et al, 2016), we controlled for employee extraversion using the Mini-IPIP scale (Donnellan et al, 2006;McDonald's Omega = 0.92). In addition, people who have positive affectivity tend to experience more positive emotions (Vandenberghe et al, 2018), which may influence the level of relational energy. Thus, we also controlled for employee positive affect using Watson et al's (1988) Positive and Negative Affect Schedule (McDonald's Omega = 0.92).…”
Section: Supplementary Analysismentioning
confidence: 99%
“…From an empirical perspective, the processual nature of our conceptual model highlights the importance of conducting longitudinal research to examine the effects of primary change appraisals on commitment to change via change-related coping, as well as to rule out potential reciprocal relationships among these variables. Moreover, as change appraisals (Kaltiainen et al , 2019), coping responses (Daniels and Harris, 2005) and organizational commitment (Vandenberghe et al , 2019) have been shown to vary across time within individuals, the adoption of longitudinal designs is suitable to detect within-person trajectories of change in these constructs. Such method of investigation is particularly relevant in the context of an ongoing organizational change, where individual psychological states are likely to vary significantly over time (Schreurs et al , 2012).…”
Section: Implications and Further Research Avenuesmentioning
confidence: 99%